2018
DOI: 10.3389/fmicb.2018.01697
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biomarkers of Marcellus Shale Activity in Pennsylvania

Abstract: Unconventional oil and gas (UOG) extraction, also known as hydraulic fracturing, is becoming more prevalent with the increasing use and demand for natural gas; however, the full extent of its environmental impacts is still unknown. Here we measured physicochemical properties and bacterial community composition of sediment samples taken from twenty-eight streams within the Marcellus shale formation in northeastern Pennsylvania differentially impacted by hydraulic fracturing activities. Fourteen of the streams w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 73 publications
(80 reference statements)
1
12
1
Order By: Relevance
“…The lowest pH value in the study (5.0) was observed in spring 2017 at Sebring Branch of Mill Run (NWIS ID 01548770), a site in the lowest sDII category with no OG or historic mining activity in its watershed and with the lowest observed specific conductance (14.7 μS/cm), suggesting that the low pH is a function of local geology, hydrology, and/or precipitation. This contrasts the findings of Chen See et al (31), Trexler et al (32), and Ulrich et al (48), which suggested that changes in pH resulting from acids used in shale gas well completion were significantly related to shale gas development in a similar geologic setting.…”
Section: Resultscontrasting
confidence: 79%
See 3 more Smart Citations
“…The lowest pH value in the study (5.0) was observed in spring 2017 at Sebring Branch of Mill Run (NWIS ID 01548770), a site in the lowest sDII category with no OG or historic mining activity in its watershed and with the lowest observed specific conductance (14.7 μS/cm), suggesting that the low pH is a function of local geology, hydrology, and/or precipitation. This contrasts the findings of Chen See et al (31), Trexler et al (32), and Ulrich et al (48), which suggested that changes in pH resulting from acids used in shale gas well completion were significantly related to shale gas development in a similar geologic setting.…”
Section: Resultscontrasting
confidence: 79%
“…This finding is consistent with ref. 31, which reports no observed changes in microbial alpha diversity with proximity to OG activity in northeastern Pennsylvania (31). No significant variation in microbial community structure was observed among sDII categories (Fig.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…For example, a halotolerant Halomonadaceae species was shown to be enriched in HF-exposed anaerobic sediments treated with DBNPA (39). Other halotolerant bacteria have also emerged as bacterial biomarkers of UOG impacts in freshwater streams (40). HF fluids contain high abundances of halophilic and halotolerant bacteria (41), which can be displaced to streams in the event of an HF fluid spill.…”
Section: Resultsmentioning
confidence: 99%